Developing marketing strategies to increase customer satisfaction - Agnes Adiniyah Putri; Iriani Iriani (Jurnal Fokus Manajemen Bisnis, 2023)
Designing a marketing strategy is creating a business plan for a company to reach potential consumers and convert them into customers of the company's products or services. The main objective of the marketing strategy itself is to achieve and communicate a sustainable competitive advantage over competing companies by understanding the needs and wants of customers and increasing service quality. This study aims to conduct an analysis and develop marketing strategies. Qualitative analysis were used in this study using servqual and strength, weakness, opportunity, treats analysis. The servqual analysis is used to measure the level of customer satisfaction, and the strength, weakness, opportunity, treats analysis is used to formulate a marketing strategy. The study's results obtained through the servqual analysis showed seven differences in negative gap values. However, two positive gap values were found in perceived importance and expectation. The strength, weakness, opportunity, treats analysis results carried out the strength-threats strategy, which includes plans to improve the characteristics of tourist objects, innovate new rides, etc.